Structure of the Velocity during a Chaotic Episode - Montenegro Joo, Javier (2015)
An investigation on the structure of the velocity in the nonlinear damped and forced oscillator, during a chaotic episode has been carried out. It has been found that the extreme values of the velocity show a bifurcating cascade as time elapses, just like the cascade detected in the extremes of oscillation amplitudes versus time, which leads to the very well-known bifurcation cascade of the periods during a chaotic event. It has been encountered that displacement and velocity during a chaotic episode in the investigated system, keep both the same structure. This similar structure detected in displacement and velocity suggests the possibility that these two magnitudes share the same pattern in other chaotic systems.